Analysis of High School Students 'Mathematic Critical Thinking Ability with Graded Response Models - Mirunnisa Mirunnisa; Zulfa Razi (Budapest International Research and Critics University, 2021)
The ability to think critically in mathematics, especially high-level mathematical critical thinking, is needed by students so that students are able to face changing circumstances or challenges that exist in life that is always developing. Graded response models (GRM) are used in order to display the estimated item parameters and students' abilities. This research is a descriptive study with a qualitative approach. Subjects in this study using SMA Simpang Tiga in terms of their mathematical critical thinking skills. Subjects were taken using a mathematical critical thinking ability test, then processed through Microsoft Excel to obtain a Graded Response Models (GRM) graph.Based on data analysis Students can be categorized as highly skilled, in general students can determine the concept of the problem correctly, are able to formulate problems in solving problems, are able to provide reasons and arguments clearly, but students are less able to evaluate problems in solving problems. Students who are categorized as having moderate ability, students can determine the concept of the problem correctly, are able to formulate problems, but students are less clear in providing reasons and arguments clearly, and are less able to evaluate the problems contained in solving problems. Students who are categorized as low, students are able to determine the concept correctly, but students are less able to formulate problems, and students are unable to provide clear reasons.